Implementation of Airway Management through Oxygen Therapy in Asthma Patients with Ineffective Breathing Pattern Nursing Problems in the Pulmonary Care Unit of BLUD RSUD Kota Baubau - Sri Resky Mustafa; Isna; Srikandi Puspa Amandaty (Indonesian Journal of Nursing and Health Care, 2026)
Background: Asthma is a chronic inflammatory disease of the airways characterized by shortness of breath, cough, and wheezing, which can result in an ineffective breathing pattern. One of the therapies used to manage this condition is oxygen therapy. Oxygen therapy, particularly using a nasal cannula, is a non-pharmacological nursing intervention aimed at improving ventilation and patients’ oxygenation status.Objective: To determine the effectiveness of oxygen therapy (nasal cannula) in improving ineffective breathing patterns in asthma patients in the pulmonary care unit of RSUD Kota Baubau.Methods: This study employed a descriptive case study design involving one patient. The instruments used included the standard operating procedure (SOP) for oxygen administration, a pulse oximeter, an observation sheet, and a nursing care format. The intervention was carried out for 3 × 24 hours, with oxygen therapy administered twice daily for 15 minutes at a flow rate of 2–4 liters per minute according to the procedure.Results: After three days of therapy from May 29 to May 31, 2025, the patient’s respiratory rate decreased from 28 breaths per minute to 23 breaths per minute. The patient’s breathing pattern improved from irregular to regular. The use of accessory respiratory muscles decreased, wheezing was still present but with reduced frequency, and complaints of shortness of breath were reduced.Conclusion: Oxygen therapy using a nasal cannula is effective in improving ineffective breathing patterns in asthma patients, as indicated by a decreased respiratory rate and improved breathing patterns. This intervention can be used as one of the nursing approaches in the management of asthma in healthcare facilities.